The Incidence of Stunting and Its Influencing Factors in Toddlers - I Kadek Wartana; Kolupe, Veni Mornalita; Fajrah, Sitti; Rabung, Alfrida Semuel (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The Sigi Regency has long struggled with a high rate of stunting among children in Central Sulawesi. There are multiple factors that play a role in contributing to this issue. Objective: The goal of this study is to examine the various factors that impact stunting in toddlers. Method: To conduct this research, a Case-control study was utilized in the Marawola Health Center Working Area in April and May of 2025. A total of 78 mothers with toddlers participated in the study, providing information through surveys and observations. The data was then analyzed using the Chi Square test with a confidence level of 95%. Result and Discussion: The results revealed that education, exclusive breastfeeding, immunization, and toddler weighing all played a significant role in the prevalence of stunting among toddlers (p value < 0.05). However, factors such as occupation, income, and access to Integrated Health Service Post did not show a significant correlation with stunting (p value > 0.05). Conclusions: It is crucial to take a comprehensive approach to health education, promote exclusive breastfeeding, conduct vaccination campaigns, and regularly monitor the growth of children in order to effectively reduce the prevalence of stunting in young children.